Reduction in lumen area is associated with the δ18O exchange between sugars and source water during cellulose synthesis. Issue 6 (10th March 2020) - Szejner, Paul; Clute, Timothy; Anderson, Erik; Evans, Michael N.; Hu, Jia
Summary: High temporal resolution measurements of wood anatomy and the isotopic composition in tree‐rings have the potential to enhance our interpretation of climate variability, but the sources of variation within the growing season are still not well understood. Here we test the response of wood anatomical features in Pinus ponderosa and Pseudotsuga menziesii, including cell‐wall thickness (CWT) and lumen area (LA), along with the oxygen isotopic composition of α‐cellulose (δ 18 Ocell ) to shifts in relative humidity (RH) in two treatments, one from high–low RH and the second one form low–high RH . We observed a significant decrease in LA and a small increase in CWT within the experimental growing season in both treatments. The measured δ 18 Ocell along the ring was responsive to RH variations in both treatments. However, estimated δ 18 Ocell did not agree with measured δ 18 Ocell when the proportion of exchangeable oxygen during cellulose synthesis ( P ex ) was kept constant. We found that P ex increased throughout the ring as LA decreased. Based on this varying P ex within an annual ring, we propose a targeted sampling strategy for different hydroclimate signals: earlier season cellulose is a better recorder of RH while late‐season cellulose is a better recorder of the source water.